Mechanisms of Thermal Tolerance in Reef-Building Corals across a Fine-Grained Environmental Mosaic: Lessons from Ofu, American Samoa - Thomas, Luke; Rose, Noah H.; Bay, Rachael A.; López, Elora H.; Morikawa, Megan K.; Ruiz-Jones, Lupita; Palumbi, Stephen R. (Frontiers in Marine Science, 2018)
Environmental heterogeneity gives rise to phenotypic variation through a combination of phenotypic plasticity and fixed genetic effects. For reef-building corals, understanding the relative roles of acclimatization and adaptation in generating thermal tolerance is fundamental to predicting the response of coral populations to future climate change. The temperature mosaic in the lagoon of Ofu, American Samoa, represents an ideal natural laboratory for studying thermal tolerance in corals. Two adjacent back-reef pools approximately 500 m apart have different temperature profiles: the highly variable (HV) pool experiences temperatures that range from 24.5 to 35°C, whereas the moderately variable (MV) pool ranges from 25 to 32°C. Standardized heat stress tests have shown that corals native to the HV pool have consistently higher levels of bleaching resistance than those in the MV pool. In this review, we summarize research into the mechanisms underlying this variation in bleaching resistance, focusing on the important reef-building genus Acropora. Both acclimatization and adaptation occur strongly and define thermal tolerance differences between pools. Most individual corals shift physiology to become more heat resistant when moved into the warmer pool. Lab based tests show that these shifts begin in as little as a week and are equally sparked by exposure to periodic high temperatures as constant high temperatures. Transcriptome-wide data on gene expression show that a wide variety of genes are co-regulated in expression modules that change expression after experimental heat stress, after acclimatization, and even after short term environmental fluctuations. Population genetic scans show associations between a corals' thermal environment and its alleles at 100s to 1000s of nuclear genes and no single gene confers strong environmental effects within or between species. Symbionts also tend to differ between pools and species, and the thermal tolerance of a coral is a reflection of individual host genotype and specific symbiont types. We conclude the review by placing this work in the context of parallel research going on in other species, reefs, and ecosystems around the world and into the broader framework of reef coral resilience in the face of climate change.